<em> </em><em>The</em><em> </em><em>probability</em><em> </em><em>of</em><em> </em><em>choosing</em><em> </em><em>the</em><em> </em><em>red</em><em> </em><em>shirt</em><em> </em><em>is</em><em> </em><em>1</em><em>/</em><em>1</em><em>0</em><em>.</em>
<em>Hope</em><em> </em><em>this</em><em> </em><em>will</em><em> </em><em>help</em><em> </em><em>u</em><em>.</em><em>.</em><em>.</em>
The equation simplified (combine like terms) would be 11x+(-24) =180.
Since adding a negative is the same as subtracting a positive, you could also write it as this: 11x-24=180. Next step is isolate the variable, so to do that you need to add 24 to both sides of the equation: 11x-24+24=180+24. This is the same as 11x=204. Now to get only one of the variable, you need to divide both sides by 11. x=18.54 repeating or x=18 6/11. Hope this helped!
Answer: 23
Step-by-step explanation:
Answer:
k(x) + g(x) = x² - 3x + 4
General Formulas and Concepts:
<u>Alg I</u>
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = 3x - 7
g(x) = 2x² - 3x + 1
h(x) = 4x + 1
k(x) = -x² + 3
<u>Step 2: Find k(x) + g(x)</u>
- Substitute: k(x) + g(x) = -x² + 3 + 2x² - 3x + 1
- Combine like terms (x²): k(x) + g(x) = x² + 3 - 3x + 1
- Combine like terms (Z): k(x) + g(x) = x² - 3x + 4
Answer:2.91666666667
Step-by-step explanation: